The Economic Life of Scholars in Rawandz 1813 - 1916 - Ahmed, Bzhar Othman; Shekh Hassan, Star; Dlawar Omar, Rebaz (IIUM Journal of Religion and Civilisational Studies, 2025)
This study seeks to examine the economic conditions and livelihood of scholars living in the city of Rawandz from 1813 to 1916, focusing on their income. During this period, scholars’ status remained intact, even enhanced, despite political changes. Since no previous study has covered this topic, this study delves into details of the economic life of scholars in Rawandz by using several untouched archives. Moreover, historical analysis, comparative methods, and scientific resources were applied in examining Ottoman documents as primary sources. The main finding of this study was that numerous Soran Emirate scholars engaged in agricultural and livestock farming instead of relying solely on their state salary. In addition, the scholars of Rawandz received a monthly salary from the Ottoman Empire, were awarded for publishing books or scientific works, and were often given seasonal food items.